2012
DOI: 10.1038/nrendo.2011.241
|View full text |Cite
|
Sign up to set email alerts
|

Effects of obesity on human sexual development

Abstract: Puberty is a period of physical and psychological maturation, with long-term effects on health. During the 20(th) century, a secular trend towards earlier puberty occurred in association with improvements in nutrition. The worldwide pandemic of childhood obesity has renewed interest in the relationship between body composition in childhood and the timing and tempo of puberty. Limited evidence suggests that earlier puberty is associated with a tendency towards central fat deposition; therefore, pubertal status … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
99
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(107 citation statements)
references
References 86 publications
4
99
1
3
Order By: Relevance
“…Several studies reported an association between overweight and early/precocious puberty (5, 33) suggesting the involvement of various environmental, genetic, and biochemical factors (5,7,17,34,35) to explain this association. However, what remains to be clarified is whether it is the high BMI that results in precocious pubertal development or is it the latter that promotes the weight gain (33,35).…”
Section: Bmi and Correlates Of Metabolic Syndromementioning
confidence: 99%
“…Several studies reported an association between overweight and early/precocious puberty (5, 33) suggesting the involvement of various environmental, genetic, and biochemical factors (5,7,17,34,35) to explain this association. However, what remains to be clarified is whether it is the high BMI that results in precocious pubertal development or is it the latter that promotes the weight gain (33,35).…”
Section: Bmi and Correlates Of Metabolic Syndromementioning
confidence: 99%
“…Nellore heifers that are heavier at 12 and 18 months go into first heat at a younger age (Alencar et al, 1987). Recent studies in humans have shown that girls with a relatively higher body mass index are more likely to menstruate early (Kaplowitz, 2008;Wagner et al, 2012). In addition to the correlation of weight gain with sexual precocity, adipose tissue has been identified as the main site of metabolism of steroid hormones (Siiteri, 1987), a factor related to the onset of reproductive activity.…”
Section: Introductionmentioning
confidence: 99%
“…However, the studies analyzing association between BMI and spermarche in boys are scare. Although previous studies have used different variables, such as voice break, age at onset of pubertal growth spurt and at peak height velocity, pubic hair development, testicular volume, and penis length to assess male puberty (9)(10)(11)(12)(13), the findings of association between BMI and those variables are controversial (9). Some studies in Europe report that estimated mean age at onset of puberty, such as age at onset of pubertal growth spurt and at peak height velocity, age of initial 4 appearance of pubic hair, and age at attainment of testicular volume above 3 ml has declined with the coincident increase in BMI (10-13), whereas among US boys a negative association has been found between boys' testicular volume and BMI (14) and higher BMI in earlier childhood may be associated with later onset of puberty which is measured by Tanner genitalia staging in a longitudinal study (15).…”
Section: Introductionmentioning
confidence: 99%